The invasion of an Atlantic Ocean river basin in Patagonia by Chinook salmon: new insights from SNPs - Ciancio Blanc, Javier Ernesto (2015)
Chinook salmon spawning was firstreported in the 1980s in the Caterina River tributaryof the Santa Cruz River basin of Patagonia, whichdrains into the Atlantic Ocean. A naturalized populationnow persists and its source has been debated.Chinook salmon from California populations wasdirectly released into the Santa Cruz River in the earlytwentieth century, but ocean ranching experiments onthe Pacific coast of Patagonia (Chile) also releasedChinook salmon of lower Columbia River origin(University of Washington hatchery stock) in the latetwentieth century. We used genetic stock identificationwith single nucleotide polymorphisms to explorethe origin of this Chinook salmon population. Thegenotypes of salmon that invaded the Santa Cruz Riverwere compared with those derived from 69 knownpopulations from the Northern Hemisphere. ChinookSalmon of the Santa Cruz River were found to be mostsimilar to those from the lower Columbia River. Thissupports the hypothesis that the Santa Cruz Riverpopulation was founded from the ocean ranching insouthern Chile and the river was invaded by fishstraying from Pacific coast basins. Moreover, we findthat the life history of these naturalized fish, as inferredfrom scale analysis, was similar to that of theprogenitor stock. We suggest that the successfulinvasion of the Caterina River in Patagonia byChinook salmon was aided by pre-adaptations ofsome of the stocks used in the ocean ranchingexperiments to conditions in the new environment,rather than a post-colonization adaptation.